Asymmetric Information, Adverse Selection and Online Disclosure: The Case of eBay Motors - Lewis, Gregory (American Economic Review, 2011)
Since Akerlof (1970), economists have understood the adverse selection problem that information asymmetries can create in used goods markets. The remarkable growth in online used goods auctions thus poses a puzzle. Part of the solution is that sellers voluntarily disclose their private information on the auction web page. This defines a precise contract – to deliver the car shown for the closing price – which helps protect the buyer from adverse selection. I test this theory using data from eBay Motors, finding that online disclosures are important price determinants, and that disclosure costs impact both the level of disclosure and prices. (JEL D44, D82, L81)